Mechanisms of Food-Induced Symptom Induction and Dietary Management in Functional Dyspepsia - Duncanson, Kerith (Nutrients, 2021)
Functional dyspepsia (FD) is a common disorder of gut-brain interaction, characterised by upper gastrointestinal symptom profiles that differentiate FD from the irritable bowel syndrome (IBS), although the two conditions often co-exist. Despite food and eating being implicated in FD symptom induction, evidence-based guidance for dietetic management of FD is limited. The aim of this narrative review is to collate the possible mechanisms for eating-induced and food-related symptoms of FD for stratification of dietetic management. Specific carbohydrates, proteins and fats, or foods high in these macronutrients have all been reported as influencing FD symptom induction, with removal of ‘trigger’ foods or nutrients shown to alleviate symptoms. Food additives and natural food chemicals have also been implicated, but there is a lack of convincing evidence. Emerging evidence suggests the gastrointestinal microbiota is the primary interface between food and symptom induction in FD, and is therefore a research direction that warrants substantial attention. Objective markers of FD, along with more sensitive and specific dietary assessment tools will contribute to progressing towards evidence-based dietetic management of FD.